Proceedings of the 2019 on Creativity and Cognition 2019
DOI: 10.1145/3325480.3325492
|View full text |Cite
|
Sign up to set email alerts
|

The Artist as Model User

Abstract: The idea of the 'model user' is well established in Computer Science. However, the usual practice of establishing a model user might not be appropriate within the context of personal data where such models are potentially limiting and exclusory. The domain of selftracking data art offers an alternative view on the concept of the Quantified Self. The model user then becomes that of the data artist. An 'edge case' where the user's representation of 'self' is determined more by creative skills and less by the too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…41 publications (8%) described or supported satisfying people's curiosity about their habits, while 25 (5%) examined external rewards such as financial payouts or discounts on insurance [46,101,119] or virtual or physical prizes [41,135,136,137]. 8 publications aimed to understand or support creative self-expression through data, such as examining artist practices with data [205] or exploring how tracked data could be incorporated into tangibles [164].…”
Section: Tracking Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…41 publications (8%) described or supported satisfying people's curiosity about their habits, while 25 (5%) examined external rewards such as financial payouts or discounts on insurance [46,101,119] or virtual or physical prizes [41,135,136,137]. 8 publications aimed to understand or support creative self-expression through data, such as examining artist practices with data [205] or exploring how tracked data could be incorporated into tangibles [164].…”
Section: Tracking Motivationmentioning
confidence: 99%
“…Opinion contributions also suggested that self-knowledge or self-understanding through numbers may be impossible [37,271] or undesirable [294], or emphasized opportunities for computing to better connect with other disciplines (e.g., sociocultural or political dimensions [179], intelligent computing [208], art [205]). Method contributions provided approaches for engaging marginalized groups in design activities to inform the design of self-tracking tools [124,150] and understanding people's in-situ habits with self-tracked data [99,167].…”
Section: Rq4: Fewer Artifact Contributions In Later Yearsmentioning
confidence: 99%